The modulatory role of short-chain fatty acids on peripheral circadian gene expression: a systematic review - dos Santos, Adriano; Vasylyshyn, Andrii (Frontiers in Physiology, 2025)
Circadian rhythm disruption significantly impacts health and causes a wide range of metabolic, cardiovascular, and psychiatric disorders. Changes in peripheral circadian clock expression are associated with the gut microbiome, particularly via the activity of short-chain fatty acids (SCFAs). The objective of this review is to explore the association between SCFA levels and peripheral circadian gene expression. This review was performed according to PRISMA guidelines. In total, eight studies were included after the PubMed database search and screening process based on inclusion and exclusion criteria. Risk of bias assessment was conducted using the SYRCLE and RoB 2 tools for animal and human studies, respectively. The results showed that propionate, acetate, and butyrate levels correlated with the expression of PER1, PER2, BMAL1, CRY1, and CRY2 in peripheral tissues, including the submandibular gland, liver, kidney, and blood serum. These findings suggest that SCFA supplementation may offer therapeutic potential for individuals with circadian misalignment, such as shift workers or patients with metabolic disorders. Although there was methodological variability among the included studies, it did not significantly compromise the overall quality of the review. The limited availability of human studies (n = 1) represents a significant constraint. Nevertheless, the findings support that SCFA supplementation may serve as a potential strategy for peripheral clock modulation. However, further human trials are needed to validate these findings in clinical settings.Systematic Review Registration:https://osf.io/6kd5q.